Preliminary Transcriptome Analysis of Mature Biofilm and Planktonic Cells of Salmonella Enteritidis Exposure to Acid Stress - Jia, Kun; Wang, Guangyu; Liang, Lijiao; Wang, Meng; Wang, Huhu; Xu, Xinglian (Frontiers in Microbiology, 2017)
Salmonella has emerged as a well-recognized food-borne pathogen, with many strains able to form biofilms and thus cause cross-contamination in food processing environments where acid-based disinfectants are widely encountered. In the present study, RNA sequencing was employed to establish complete transcriptome profiles of Salmonella Enteritidis in the forms of planktonic and biofilm-associated cells cultured in Tryptic Soytone Broth (TSB) and acidic TSB (aTSB). The gene expression patterns of S. Enteritidis significantly differed between biofilm-associated and planktonic cells cultivated under the same conditions. The assembled transcriptome of S. Enteritidis in this study contained 5442 assembled transcripts, including 3877 differentially expressed genes (DEGs) identified in biofilm and planktonic cells. These DEGs were enriched in terms such as regulation of biological process, metabolic process, macromolecular complex, binding and transferase activity, which may play crucial roles in the biofilm formation of S. Enteritidis cultivated in aTSB. Three significant pathways were observed to be enriched under acidic conditions: bacterial chemotaxis, porphyrin-chlorophyll metabolism and sulfur metabolism. In addition, fifteen differentially expressed novel non-coding small RNAs (sRNAs) were identified, and only one was found to be up-regulated in mature biofilms. This preliminary study of the S. Enteritidis transcriptome serves as a basis for future investigations examining the complex network systems that regulate Salmonella biofilm in acidic environments, which provide information on biofilm formation and acid stress interaction that may facilitate the development of novel disinfection procedures in the food processing industry.